2013
DOI: 10.2217/pgs.13.160
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variations of Human CYP2D6 in the Chinese Han Population

Abstract: This study provides the most comprehensive data concerning CYP2D6 polymorphisms in the Chinese Han population to date and increases the number of known alleles; these findings may greatly contribute to the development of personalized medicine for the Chinese Han population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
66
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 43 publications
6
66
2
Order By: Relevance
“…It has been reported that the allele CYP2D6*92 (1995delC) results in a 654delC mutation in the cDNA sequence and that this mutation is predicted to cause a pre-termination and thus code for a truncated protein with a molecular weight of 25 kDa. Similarly, another allelic variant, CYP2D6*96 (3895C>T), carries one nucleotide change in cDNA at position 1270 (C>T) and results in another pre-stop mutation, 424STOP, at the amino acid level [12]. Based on the expression pattern in mammalian cells, our results revealed that the majority of tested CYP2D6 variants expressed proteins of 55.7 kDa, while the variants CYP2D6*92 and CYP2D6*96 were translated into two truncated proteins of 25 and 47.5 kDa, respectively; these values were equal to their estimated molecular weights ( fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that the allele CYP2D6*92 (1995delC) results in a 654delC mutation in the cDNA sequence and that this mutation is predicted to cause a pre-termination and thus code for a truncated protein with a molecular weight of 25 kDa. Similarly, another allelic variant, CYP2D6*96 (3895C>T), carries one nucleotide change in cDNA at position 1270 (C>T) and results in another pre-stop mutation, 424STOP, at the amino acid level [12]. Based on the expression pattern in mammalian cells, our results revealed that the majority of tested CYP2D6 variants expressed proteins of 55.7 kDa, while the variants CYP2D6*92 and CYP2D6*96 were translated into two truncated proteins of 25 and 47.5 kDa, respectively; these values were equal to their estimated molecular weights ( fig.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, 22 new nonsynonymous, mutated sites were found, and 12 of them were designated as novel alleles (*87-*93, *94A, *94B and *95-*98) by the Human CYP Allele Nomenclature Committee [12]. Considering the fact that there are more than 1.4 billion people living in the mainland of China, it is urgent to investigate the functional characterizations of these newly identified CYP2D6 variants, although the allele frequency of each variant is below 1% [12]. In this study, we expressed all of these novel allelic variants in 293FT cells and systematically evaluated their enzymatic activities towards two typical probing substrates, dextromethorphan and bufuralol.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous study from our laboratory, we performed a large-scale genetic research of polymorphisms of CYP2D6 in 2129 randomly healthy Chinese Han subjects (Qian et al 2013). Among these novel mutation sites, 22 were nonsynonymous and 12 were named as novel alleles by the Human CYP Allele Nomenclature Committee.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, 22 new nonsynonymous, mutated sites were found (Qian et al 2013), 12 of them were defined as the novel alleles (*87-*93, *94A, *94B and *95-*98) by the Human CYP Allele Nomenclature Committee. Even though the frequency of genetic polymorphism of enzyme CYP2D6 is very low, based on that China has a population of 1.4 billion.…”
Section: Introductionmentioning
confidence: 99%